1991
DOI: 10.1063/1.349614
|View full text |Cite
|
Sign up to set email alerts
|

Autoresonance microwave accelerator

Abstract: A novel autoresonance acceleration scheme comprising a traveling electromagnetic wave and a magnetostatic field is discussed. A spatially tailored magnetostatic field keeps the electron in a constant phase and allows continuous acceleration. Numerical results are presented. Experimental results, showing acceleration from an initial value of 10 keV to energies of about 150 keV after 1.5 m by using a pulsed 50-kW peak power transmitter, are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
3

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 9 publications
0
14
0
3
Order By: Relevance
“…Это связано с тем, что релятивистское изменение циклотронной частоты ком-пенсируется доплеровским сдвигом частоты волны [8,9]. Существование циклотронного авторезонанс-ного механизма ускорения электронов электромагнитными волнами микроволнового диапазона было доказано экспериментально в работах [10][11][12][13][14][15][16][17]. Эксперименты показали также, что возможно значитель-ное ускорение заряженных частиц в условиях, отличных от идеализированных условий авторезонанса.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Это связано с тем, что релятивистское изменение циклотронной частоты ком-пенсируется доплеровским сдвигом частоты волны [8,9]. Существование циклотронного авторезонанс-ного механизма ускорения электронов электромагнитными волнами микроволнового диапазона было доказано экспериментально в работах [10][11][12][13][14][15][16][17]. Эксперименты показали также, что возможно значитель-ное ускорение заряженных частиц в условиях, отличных от идеализированных условий авторезонанса.…”
Section: Introductionunclassified
“…При этом было обна-ружено, что должны выполняться исключающие друг друга требования: с одной стороны, для увеличе-ния темпа ускорения необходимо увеличение напряжённости электрического поля ускоряющей волны, а это, с другой стороны, приводит к нарушению режима устойчивого ускорения. Поэтому при авторезо-нансном ускорении в волноводе необходим подбор оптимальных параметров волны и условий инжек-ции [14,15]. Эксперименты [16] показали, что циклотронное авторезонансное ускорение электронов в волноводе с полем моды ТЕ 11 происходит с очень высокой эффективностью: более 90% мощности ВЧ-поля волновода передаётся ускоряющемуся электронному пучку.…”
Section: Introductionunclassified
“…This particular condition is the one requiring the laser field to be dispersionless [4], a very restrictive condition if one takes into account dispersive effects arising from the confining wave guides [5]. The analysis of dispersive CRLA's has been recently carried out both analytically (in a perturbative fashion) [6] and numerically [4], where it was shown that a typically small degree of dispersion may create some severe limits to the accelerating efficiency.…”
mentioning
confidence: 99%
“…Although recent proof-ofprinciple experiments- 7 have successfully demonstrated the acceleration of electrons to moderately relativistic energies using microwaves and the technique of tapering the guide field, there are severe limitations posed by laser field dispersion, synchrotron radiation losses, and the available strength of magnetic field in laboratories.…”
mentioning
confidence: 99%